Classism Hate Speech in Katherine Mansfield's Short Story ‘The Doll’s House’: A Pragmatic Study: ايمان نوري جاسم , مصلح شويش احمد (Journal of the College of Education for Women, 2021)
Hate speech (henceforth HS) has recently spread and become an important issue. This type of speech in children's writings has a particular formulation and specific objectives that the authors intend to convey. Thus, the study aims at examining qualitatively and quantitatively the classism HS and its pragmatic functions via identifying the speech acts used to express classism HS, the implicature instigated as well as impoliteness. Since pragmatics is the study of language in context, which is greatly related to the situations and speaker’s intention, this study depends on pragmatic theoriespeech acts, impoliteness and conversational implicature) to analyze the data which are taken from Katherine Mansfield's short story (The Doll’s House). The data has been analyzed qualitatively and quantitatively. It is qualitative, as it is dedicated to describe HS phenomenon that is found in the selected short story, depending on an eclectic model. Regarding the quantitative analysis, the researchers have used SPSS 23 program to determine the frequencies and percentages of the strategies that are intended to be measured. The study has concluded that HS has multiple dimensions that are difficult to interpret outside the context of speech. It can be conveyed by many strategies, both explicit and covert. Further, the simplest form of HS involves an insult in addition to other functions, such as disapproval and humiliation.